g) 6xy^2 = (3x) (?)
6xy^2 = 3*2*x*y^2
Now, the commutative property of multiplication says you can rearraneg those factors as you like. So, you can also write it as
3*x*2*y^2 = (3x)(2y^2)
h) 25a^3b^2 = (5a^2b^2) (5a)
i) 6x + 6y + 6p = 6(x+y+p)
because of the distributive property
Factor by identifying a common factor in each term.
g) 6xy2 = (3x) (?)
h) 25a3b2 = (5a2b2) (?)
i) 6x + 6y + 6p
need help please ?
2 answers
g. 6xy^2 = 3x.
6xy^2 - 3x = 0,
3x(2y^2 - 1) = 0.
h. 25a^3b^2 = 5a^2b^2.
25a^3b^2 - 5a^2b^2 = 0,
5a^2b^2(5a - 1) = 0.
I. 6x + 6y + 6p.
6(x + y + p).
6xy^2 - 3x = 0,
3x(2y^2 - 1) = 0.
h. 25a^3b^2 = 5a^2b^2.
25a^3b^2 - 5a^2b^2 = 0,
5a^2b^2(5a - 1) = 0.
I. 6x + 6y + 6p.
6(x + y + p).